Common Sense, the Common Reader, and Human Nature: David Hume’s «kind of Unity» - Loretelli, Rosamaria (Diciottesimo Secolo, 2025)
This article presents a close reading of the three pages of the third section of An Enquiry Concerning Human Understanding which were eliminated in the 1777 edition, the first to be published after Hume’s death. These pages deserve attention, since their subject is narrative, an art which Hume had not dealt with elsewhere. Here, after having radically rejected the rules of the past, Hume proposes new rules based on his science of human nature, giving them philosophical foundation. He explains what discursive forms enliven the readers’ imagination and kindle their passions. In short, he discloses a perspective reader response: not of learned readers though, but of all readers, of the common reader of his time. And that reader had an approach to the practice which was different from before, having internalized silent and individual reading. In eighteenth-century Western Europe, as the article concisely illustrates at the beginning, that practice spread among the majority of the literate population. Such is the reader Hume sets at the centre of his inquiry, one whose approach to the narrative text was direct, and no longer mediated by the voice and the gestures of the person reading aloud. Hume’s was the type of reader that contemporary writers of “compositions of genius”, to use a Humean expression, were starting to envisage for their narratives and theories.